Investigating the effect of magnetic force on the flow behavior of pipeline - Ramanathan, Geetha (2012)
Drag forces has been the main problem that occurs in pipeline and loss energy due to the water transmission along the pipeline.During the transmission of water in the pipeline,it needs high consumption of pumping power in the pipeline due to the fluids are flow in order of turbulent flow by against the fluid friction,which has been happened in the pipeline wall and results in drag forces of the pipeline.Consequently,the drag forces in the pipeline can be reduced by addition of drag reducing agent to improvise the fluid transmission in pipeline.The purpose of this research work is to study the effect of particle size and concentrations of suspended solid such as iron powder applied to magnetic force flow and ultimately investigate the flow behaviour in multi phase flow in the pipeline.In this study,the investigation is based on the role of ferromagnetic powder such as iron powder used as drag reduction agent to reduce the drag forces and less turbulent in the fluid transmission pipeline. In the experimental work,check the flow behaviour of pipeline when the iron powders add to the fluid transmissions with concentration of 100ppm, 300ppm and 500ppm and provided with and without magnetic force.Moreover,portable magnetic device has been used to apply magnetic force to the flow in the pipeline. The experimental procedures carried out in an experimental rig and obtain the pressure drop readings for drag reduction calculation.Iron powder particles are suitable and best method for drag reducing agent.In addition,smaller particle size at high concentration able to show the higher drag reduction compared to bigger particle size.The turbulence flow of the pipeline can be reduced by appliance of magnetic field and the high power of magnetic force able to reduce the drag reduction at higher Reynolds number.The average value of drag reduction for the pipe length of 1.5m was recorded for iron powder of particle size of 60µm is 25% and particle size of 120µm was achieved about 10% for concentration of 300ppm with the magnetic power of 720W.